Obsessive-compulsive skin disorders: a novel classification based on degree of insight. (19th May 2017) - Zhu, Tian Hao; Nakamura, Mio; Farahnik, Benjamin; Abrouk, Michael; Reichenberg, Jason; Bhutani, Tina; Koo, John
Abstract: Individuals with obsessive-compulsive features frequently visit dermatologists for complaints of the skin, hair or nails, and often progress towards a chronic relapsing course due to the challenge associated with accurate diagnosis and management of their psychiatric symptoms. The current DSM-5 formally recognizes body dysmorphic disorder, trichotillomania, neurotic excoriation and body focused repetitive behavior disorder as psychodermatological disorders belonging to the category of Obsessive-Compulsive and Related Disorders. However there is evidence that other relevant skin diseases such as delusions of parasitosis, dermatitis artefacta, contamination dermatitis, AIDS phobia, trichotemnomania and even lichen simplex chronicus possess prominent obsessive-compulsive characteristics that do not necessarily fit the full diagnostic criteria of the DSM-5. Therefore, to increase dermatologists' awareness of this unique group of skin disorders with OCD features, we propose a novel classification system called Obsessive-Compulsive Insight Continuum. Under this new classification system, obsessive-compulsive skin manifestations are categorized along a continuum based on degree of insight, from minimal insight with delusional obsessions to good insight with minimal obsessions. Understanding the level of insight is thus an important first step for clinicians who routinely interact with these patients.